Context awareness through identifying user activities and positioning - Rahman, M.M. Hafizur; Ayu, Media Anugerah; Abdul Matin, Ahmad Faridi (2014)
Context awareness is an important element in the pervasive and ubiquitous computing. It involves the ability of the computing system to be aware of the context in which a particular target user is experiencing. This involves the location in which the target is, the activity that the target is doing, the identity of that target and the time in which the activity occur. The focus of the project is to determine the location and activity aspects that would be utilized in the prediction of the context of the user. It has been shown that accelerometer data could be used for activity recognition. i.e. knowing the user’s activities such as walking, standing, sitting etc. However, user location could be found using various methods, Geo-location being one of these methods. Once these two elements are known we propose the use of HMM to predict the context of the user.